Dual energy CT in clinical practice - Johnson, Thorsten R. C.; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Dual-energy CT is a novel, rapidly emerging imaging technique which offers important new functional and specific information. With implementation of the technology in commercially available scanners, many clinical applications are now feasible. In this book, physicists and specialists from different CT manufacturers provide an insight into the technological basis of, and the different approaches to, dual-energy CT. Renowned medical scientists in the field explain the pathophysiological and molecular background of the technique, discuss its applications, provide detailed advice on how to obtain optimal results, and offer hints regarding clinical interpretation. The main focus is on the use of dual-energy CT in daily clinical practice, and individual sections are devoted to imaging of the vascular system, the thorax, the abdomen, and the extremities. Evaluations and recommendations are based on personal experience and peer-reviewed literature. Plenty of carefully chosen high-quality images are included to illustrate the clinical benefits of the technique.
Physical Background -- Dual Source CT -- Dual Layer CT -- Gemstone Detector: Dual Energy Imaging via Fast kVp Switching -- Dual-Energy Algorithms and Postprocessing Techniques -- Head and Neck -- Aorta -- Peripheral Arteries -- Plaque Differentiation -- Lung Perfusion -- Lung Ventilation -- Pulmonary Nodules and Lung Cancer -- Myocardial Perfusion -- Neurological Applications -- Liver Imaging -- Kidney Imaging -- Pancreas -- Kidney Stones -- Tendons and Ligaments -- Gout.
Electronic reproduction.
Keywords: Tomography; Tomography, X-Ray Computed -- trends; Electronic books